2002
DOI: 10.1128/iai.70.5.2288-2296.2002
|View full text |Cite
|
Sign up to set email alerts
|

Gender Is a Major Determinant of the Clinical Evolution and Immune Response in Hamsters Infected withLeishmaniaspp

Abstract: In regions where leishmaniasis is endemic, clinical disease is usually reported more frequently among males than females. This difference could be due to disparate risks of exposure of males and females, but genderrelated differences in the host response to infection may also play a role. Experimental studies of the influence of gender on Leishmania infection have not included parasites of the subgenus Viannia, which is the most common cause of cutaneous leishmaniasis in the Americas. Mice are not readily susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
106
3
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(123 citation statements)
references
References 40 publications
6
106
3
6
Order By: Relevance
“…An additional factor in the success of the current model is the use of male hamsters (29). It was previously demonstrated that host gender has a significant influence on the clinical evolution and immunological response to Leishmania (Viannia) infection (29). Taken together, we were able to reliably and reproducibly bring about a rapid onset of progressive disease in 3-to 4-month-old hamsters.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…An additional factor in the success of the current model is the use of male hamsters (29). It was previously demonstrated that host gender has a significant influence on the clinical evolution and immunological response to Leishmania (Viannia) infection (29). Taken together, we were able to reliably and reproducibly bring about a rapid onset of progressive disease in 3-to 4-month-old hamsters.…”
Section: Discussionsupporting
confidence: 51%
“…In the current model, the rapid onset of clinical symptoms in older hamsters could be the result of the inoculation of parasites in a highly vascularized tissue (the ear) facilitating visceralization and establishment of disease. An additional factor in the success of the current model is the use of male hamsters (29). It was previously demonstrated that host gender has a significant influence on the clinical evolution and immunological response to Leishmania (Viannia) infection (29).…”
Section: Discussionmentioning
confidence: 99%
“…This difference could be caused by sex-related higher susceptibility to the disease, which has been suggested in animal studies in a hamster model. 36 Additionally, a continuous increase in the strength of association between age and prevalence for cases in persons > 15 years of age was also observed. This increase may be related to the inception or intensification of labor and recreational activities (e.g., fishing and hunting) in younger persons.…”
Section: Discussionmentioning
confidence: 93%
“…Neither IFA positivity at initial diagnosis, nor the time of the first return for evaluation of treatment, were found to be factors associated with the healing of lesions. No differences in lesion healing between men and women were found, despite the findings of Travi et al (2002), who studied hamsters infected with Leishmania (Viannia) and observed that the immune response was more permissive to infection among males than females. The factors that contribute to the cutaneous disease evolving into one of the later forms are not fully understood, but delay in healing the first lesion and inadequate treatment are both known predictors (Carvalho et al, 1995).…”
Section: Discussionmentioning
confidence: 43%